Effect of Impella During Veno-Arterial Extracorporeal Membrane Oxygenation on Pulmonary Artery Flow as Assessed by End-Tidal Carbon Dioxide. Issue 4 (July 2018) - Eliet, Jacob; Gaudard, Philippe; Zeroual, Norddine; Rouvière, Philippe; Albat, Bernard; Mourad, Marc; Colson, Pascal H.
Abstract : Peripheral veno-arterial extracorporeal membrane oxygenation (VA ECMO) exposes the patient to a pulmonary blood flow bypass and a left ventricle afterload increase. Impella, a catheter-mounted microaxial rotary pump, has been proposed for left ventricle (LV) unloading in combination with VA ECMO. In order to assess the effect of Impella on pulmonary flow and LV preload, we checked Doppler pulmonary artery velocity–time integral (pVTI) and LV diastolic diameter (LVED) by transesophageal echocardiography and end-tidal carbon dioxide (EtCO2 ) during a step-by-step increase in Impella flow (Impella ramp test). From 134 patients on VA ECMO retrieved from our database, 27 (20%) have benefited secondary Impella implantation, out of which 11 patients had available EtCO2, pVTI, and LVED measurements at various levels of Impella speeds. We observed a proportional increases in pVTI and EtCO2 and decrease in LVED ( p ⩽ 0.001) during Impella flow increase. There was a significant correlation between EtCO2 and pVTI (Pearson correlation coefficient 0.64; p = 0.006). The study shows that Impella improves pulmonary flow, an effect that can be easily measured by EtCO2 monitoring, and ensures LV discharge, allowing adapting Impella flow adequately to patient's individual needs.